A flexible operating tool to provide an efficient project's staffing and resource allocation. (29th November 2021) - Bertolini, Massimo; Neroni, Mattia; Zammori, Francesco
Resource allocation is paramount for the success of complex projects; many allocation and staffing models have been proposed in the literature, but none of them has found its way into practice yet. Hence, we propose a tool to provide an efficient project's staffing and resource allocation, with the goal to create cohesive teams, and an almost perfect matching among time/quality requirements and resources' skills. To achieve this objective, the tool makes use of a specific heuristic that reproduces the reasoning of the project manager, using logical rules based on sorting and prioritising criteria, both for tasks and resources. To validate the tool, we applied it to a comprehensive set of past projects, completed by a consultant company over the past five years. Solutions provided by our tool were assessed by a team of experienced project managers, and they were found superior to the ones originally implemented by the company.